PCNL Surgery Following Laparoscopic Hellström Pyeloplasty in a Patient with UPJO and Concurrent Renal Stones - Hormoz Karami; Omid Aminirad (Case Reports in Clinical Practice, 2024)
The prevalence of renal stones with concomitant UPJO is about 20-30%. Its treatment method is controversial. In this study, a 29-year-old man with UPJO and simultaneous ipsilateral renal stone is presented, who was treated with PCNL following Hellström laparoscopic pyeloplasty.